Stem Cell Therapies for Spinal Cord Injury - A Review - Filip Borodziuk; Barbara Borodziuk; Katarzyna Ciuba; Paulina Dąbrowska; Michał Żuber; Karol Bochyński; Katarzyna Molenda; Michał Dacka; Kamila Giżewska; Konrad Białogłowski (Nicolaus Copernicus University in Toruń, 2024)
The escalating incidence of Spinal Cord Injury (SCI), with approximately 0.9 million cases globally, underscores its growing public health concern. Traumatic SCI, often prevalent in developing nations due to factors like motor vehicle accidents and falls, leads to secondary damage involving inflammation, neuronal death, and ionic dysregulation. Despite the absence of an effective treatment for SCI, Stem Cell Therapy (SCT) emerges as a promising avenue, harnessing stem cells' unique capabilities for regeneration and replacement. The review explores various stem cell types, such as Neural Stem/Progenitor Cells (NS/PCs), Embryonic Stem Cells (ESCs), Induced Pluripotent Stem Cells (iPSCs), and Mesenchymal Stem Cells (MSCs), detailing their potential in preclinical and clinical contexts. Specifically, NSCs exhibit therapeutic promise by modulating astrocyte contribution, enhancing differentiation, and promoting growth factors. ESCs, despite their pluripotency, face ethical concerns and potential teratocarcinoma formation. IPSCs, reprogrammed from somatic cells, showcase potential in treating SCI without ethical issues. MSCs, with diverse sources like bone marrow, umbilical cord, and adipose tissue, offer versatility in differentiation and therapeutic benefits. Clinical trials with MSCs, especially BM-MSCs, UC-MSCs, and AD-MSCs, demonstrate improvements in motor and sensory functions, highlighting their regenerative potential. Despite promising results, challenges such as potential tumorigenesis and high costs persist, warranting further exploration and clinical translation of these stem cell therapies for SCI.